Perancangan Alat Bantu Angkut Komponen Motor Modular Menggunakan Metode Quality Function Deployment (QFD) di Bengkel Cat Yoesbrush - Muhammad Hidayah Tullah; Brillian Nur Diansari; Garnet Filemon Waluyono (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Bengkel Cat Yoesbrush operates two work locations about 600 meters apart and relies on a single Honda Astrea motorcycle to move components between branches, forcing staff to make 10-20 round trips daily because the standard vehicle's limited cargo space cannot accommodate heterogeneous loads that combine bulky-but-light parts with heavy components. This study designs a modular motorcycle component transport attachment using the Quality Function Deployment (QFD) method to translate user needs into technical specifications. Primary data were collected through questionnaires and interviews with two direct users and validated by an expert, then processed through a House of Quality (HoQ) matrix and visualized in SolidWorks. The results identify 11 customer requirement attributes (WHATs) and 13 technical responses (HOWs), with the highest priorities being rack dimensions (13%), mounting points (10%), and maximum load capacity (10%). The final design is a 60x70 cm modular rack built from 2 mm hollow steel, capable of carrying at least 30 kg, weighing under 10 kg in total, and fitted with a knock-down bracket system requiring no permanent modification to the motorcycle.